Digitalization impact estimation on the economic growth of the European countries - I. V. Somina; S. P. Gavrilovskaya (Вестник университета)
The article deals with an attempt to assess an impact of digitalization on the economic development of the European countries. For these purposes, it is proposed to supplement the classical Cobb-Douglas production function with a digital capital parameter. However, the study showed the problem of absence of a representative statistical base for the cost estimation of the digital capital of the European countries. Under these conditions, method for the impact assessment of digitalization on the indicators of the countries’ economic growth was developed, based on the application of the rating correlation analysis to the classical production function calculations results and the business digitalization index. In general, the results of the performed calculations confirmed the positive impact of business digitalization on the economic growth of the European countries and made it possible to estimate the nature of the digital processes’ impact on the main production factors – labor and fixed asset. The prospects for further development of this subject should be associated with the scientific grounds of the general approaches to estimating digital capital and the formation of the corresponding statistical arrays.